Pengaruh Mendengarkan Murattal Surat Ar Rahman Terhadap Kualitas Tidur Pasien Sindrom Koroner Akut - Ahmat Pujianto; Titis Kurniawan; Helwiyah Ropi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
One of the negative effects of the hospitalization process is low sleep quality. Low sleep quality in patients with ACS may increase stress, anxiety, and depression that potentially worsening patients’ chest pain. This study aimed to determine the effect of listening Surat Ar Rahman recital holy Qur’an on sleep quality in patients with ACS in the cardiac intensive unit. This study was quasi experiment with nonequivalent control group design. Thirty-six respondents were recruited purposively and divided into intervention (18 respondents) and control group (18 respondents) with matching in anxiety level. The intervention group received therapy listening Surat Ar Rahman recital holy Qur’an for 15 minutes before nocturnal sleep. Sleep quality measured using Richard Campbell Sleep Questionnaire (RCSQ) instrument. Collected data were analyzed using dependent and independent sample t test. The level of significance was set at p